Pengaruh Model Pembelajaran Game Based Learning Berbantuan Aplikasi Wayground Terhadap Hasil Belajar Ekonomi Siswa Fase F SMA N 1 Kinali - Alexius Widiawan; Jean Elikal Marna; Khairi Murdy (Universitas Negeri Padang, 2026)
This study aims to analyze the effect of the Game Based Learning model assisted by the Wayground application on students’ learning outcomes in economics. This research uses a quantitative approach with a quasi-experimental design, specifically a pretest-posttest control group design. The population consists of all students of class XI Fase F at SMA Negeri 1 Kinali, with samples selected using purposive sampling technique, resulting in class XI Eko 2 as the experimental class and XI Eko 1 as the control class. The researcher gathered data through tests consisting of pretest and posttest and analyzed using an independent sample t-test. The results are expected to show that the implementation of Game Based Learning assisted by Wayground can improve students’ learning outcomes compared to conventional learning methods. It can be concluded that Game-based learning assisted by the Wayground application contribute positively to improving students’ academic achievement.